Concept difficulty in secondary school chemistry: An intra-play of gender, school location and school type - Adekunle Ibrahim Oladejo; Ibukunolu A. Ademola; Musa Adekunle Ayanwale; Tobih Deborah O. (OmniaScience, 2023)
This study focused on addressing underperformance in chemistry in Anglophone West African countries. The main purpose of the study was to determine if factors such as gender, school location and ownership impact students' perception of the difficulty of chemistry concepts and to suggest how these difficult concepts can be made easy to learn from the perspectives of the students. A mixed-methods approach was adopted. Participants were 1,292 chemistry students from nine public and 12 private secondary schools in Nigeria and Ghana with about three-quarters of the schools from urban areas. About 51% of the participants were females. Twenty-four students were interviewed to gather qualitative data. The Difficult Concept in Chemistry Questionnaire (DCCQ) and the Difficult Concepts in Chemistry Interview Guide (DCCIG) were used for data collection. The test-retest reliability coefficient of the DCCQ was 0.88. We found a slight difference in the perception of male and female students while school type came as a major determinant factor on students' perception of difficult concepts in chemistry, just as school location. Phobia for calculations came out as a major cause of difficulty in the top five perceived difficult concepts. Findings on causes of learning difficulties were reported as well as suggestions for improvement as viewed by the students. Recommendations were made for improving the teaching and learning of chemistry in Anglophone West African schools.